On the Issue of Pre-Contractual Liability Qualification - L. V. Shvarts (Теоретическая и прикладная юриспруденция)
The article is devoted to the study of the existing positions in the Russian doctrine regarding the institution of precontractual liability. The ambiguous position of the legislator, the controversial explanations of the judges of the Supreme Court of the Russian Federation do not reduce the relevance of the problem of the unified nature of pre-contractual liability. In this article, the author points out the shortcomings of the legal regulation of determining the time and grounds for applying pre-contractual liability measures, as well as issues of determining a specific mechanism for protecting bona fide negotiators, in particular in the field of identifying the rules for calculating losses incurred.